2020
DOI: 10.2139/ssrn.3553245
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and the Equity Home Bias Puzzle

Abstract: The views expressed in this paper are those of the authors and do not necessarily reflect those of the Deutsche Bundesbank, the Banco de España or the Eurosystem. We would like to thank seminar participants at the Banco de España and an anonymous referee for their comments, as well as Masashige Hamano for sharing his codes with us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…We justify our modelling choice as the minimal specification that is necessary to account for the obvious fact that recessionary episodes come with very different growth rates of the GDP, and other real activity indicators. On the one hand, the Global Financial Crisis of [2007][2008] was unusually severe for many economies that, compared to it, subsequent recessions look barely distinguishable from normal times. For example, based on the data for many European countries, one would almost certainly fail to detect any other recession but the one observed upon the Global Financial Crisis when using a Markov-switching model with the common factor of the Hamilton type.…”
Section: Inferring Heterogeneous Recessionsmentioning
confidence: 99%
See 4 more Smart Citations
“…We justify our modelling choice as the minimal specification that is necessary to account for the obvious fact that recessionary episodes come with very different growth rates of the GDP, and other real activity indicators. On the one hand, the Global Financial Crisis of [2007][2008] was unusually severe for many economies that, compared to it, subsequent recessions look barely distinguishable from normal times. For example, based on the data for many European countries, one would almost certainly fail to detect any other recession but the one observed upon the Global Financial Crisis when using a Markov-switching model with the common factor of the Hamilton type.…”
Section: Inferring Heterogeneous Recessionsmentioning
confidence: 99%
“…Dynamic factor models have been widely applied to the U.S. economy since it has been shown that they provide both accurate forecasts of GDP growth and inferences on the state of the economy in a real-time environment. On the one hand, Giannone et al (2008) and Banbura et al (2012), among others, have relied on linear factor models, that allow for mixed frequency data, to provide short-term forecasts of real GDP. On the other hand, Chauvet (1998) employs single-frequency nonlinear factor models, where the factor is subject to regime changes, with aim of providing timely inferences on turning points.…”
Section: The Case Of the United Statesmentioning
confidence: 99%
See 3 more Smart Citations